What we hoped for and what we achieved: Tax performance of Semi‐Autonomous Revenue Authorities in sub‐Saharan Africa. (4th June 2021) - Jeppesen, Matilde
Abstract: Semi‐Autonomous Revenue Authorities (SARAs) have been introduced widely in the Global South with the hope of improving tax performance. However, while implementing the reform is an extensive restructuring and expensive endeavour, there is scarce systematic information on how SARAs have actually performed. This paper examines the average tax performance effect of introducing a SARA in sub‐Saharan Africa and finds a positive effect on direct tax revenue, but no effect on indirect or total tax revenue. This is significant as it implies that implementing a SARA is not a quick‐fix solution to improving total tax performance, but it does still offer some advantages. Additionally, the heterogeneous effects on direct and total tax revenue highlight the importance of how tax performance is evaluated.